Photo-driven Fischer–Tropsch synthesis. Issue 46 (17th November 2020) - Wu, Hua-Kun; Zhang, Fan; Li, Jing-Yu; Tang, Zi-Rong; Xu, Yi-Jun
Abstract : Photo-driven Fischer–Tropsch synthesis (FTS) provides a attractive and sustainable alternative compared to traditional FTS. This minireview expatiates the recent advances of various metal-based catalysts for photo-driven FTS. Abstract : Heterogeneous catalytic conversion of syngas (including CO and H2 ) derived from carbon-rich resources ( e.g., natural gas, coal, and biomass) to desired liquid fuels or valuable chemicals, well known as Fischer–Tropsch synthesis (FTS), is of great significance to alleviate the dependence of petroleum. Traditional industrial FTS requires harsh reaction conditions and the chain length distribution of products represents a broad and non-selective Anderson–Schulz–Flory distribution. In contrast, using solar energy and suitable photocatalysts to effectively promote FTS with considerable selectivity toward target products under mild conditions is a more attractive and sustainable alternative. This timely minireview aims to expatiate the recent advances of various transition metal-based catalysts for photo-driven FTS to obtain fuels and commodity chemicals. We put dedicated emphasis on the rational photocatalyst design, structure–performance relationships, and reaction mechanisms in this context. Finally, the current challenges and perspectives for future research in this nascent and promising field of photo-driven FTS are also discussed.